Escola e estetização: Possíveis - Pereira, Marcos Villela (Diálogos Latinoamericanos, 2014)
Abstract: Aesthetics, on this essay, is understood as a mode of existence which implies a set of attributes, values and perspectives/possibilities for action, without reducing to any such strongholds. Therefore, I reiterate the understanding that aesthetics, politics and ethics, even if specific fields and irreducible to each other, are inseparable. The aestheticization concerns the effects that the experience produces the consciousness that constitute the subject’s self, of others and the world, that is, concerns the ways that the subject assumes the decisions you make, the judgments that gives at attitudes that performs at the choices they make, the ideas you have, the conclusions we reach. The aestheticization has close relation with the experience leaves traces in the subject, so that it constitutes an affirmative answer (meaning reiterate, join or postulate) or negative (meaning prohibit, reject, discard) these criteria, principles and values. The school, in turn, is an agency of cultural production and reproduction. Your main goal while teaching institution, is to transmit knowledge, skills and abilities develop, produce tastes, subsidize arguments, disciplinary bodies and behaviors and cognitive-intellectual meet needs in populations that her access. Here I try to focus mainly functions educative, instructive and formative. Its operation is intended to ensure the homogenization of large groups of people in order to unify practices, habits, customs, values and ways of thinking. I call this form of the aestheticization induce or act upon the world and subject to lead them to a certain ethical performance and policy within the collective life. Examine the operations aestheticizing means school study how the operation of various devices takes the configuration of